BIOSURFACTANT AS BIOFILM ERADICATION AGENT AND ITS EFFECT ON BIOCORROSION OF CARBON STEEL ST37 UNDER STATIC AND DYNAMIC FLOW CONDITION - ARDINI FAUZIYYAH (NIM: 21117032), NABIILAH
Biocorrosion is the deterioration of metals by microorganisms which are commonly found in the form of biofilm on the oil industry pipeline. High dose of synthetic antimicrobial is used to eradicate biofilm in order to combat biocorrosion, but such treatment is detrimental to the environment. Recent research shows that biosurfactant have anti-biofilm activity to inhibit and eradicate biofilm formation on material. Environment-friendly properties of biosurfactant makes it a potential candidate to replace synthetic antimicrobial and combat biocorrosion. The ability of biosurfactant to eradicate biofilm of natural consortium in various flow condition and its effects on corrosion rate need to be studied. This study aims to determine the ability of biosurfactant produced by indigenous oil reservoir bacteria to eradicate biofilm of bacterial consortium that grow in brine water in static and dynamic flow condition. This research was conducted through the formation of biofilm on Carbon Steel ST37 in static and dynamic flow. Eradication of biofilm is performed by exposing biosurfactant to mature biofilm. Eradication ability of biosurfactant were analyzed by calculating biofilm wet weight on steel before and after eradication. Community dynamics of biofilm were analyzed using total plate count method. Corrosion rate were determined by weight-loss method. Visualization of corrosion product and biofilm on steel were performed using Scanning Electron Microscopy - Energy Dispersive X-ray Spectroscopy (SEM-EDS). Biofilm maturation in static and dynamic flow were achieved on the 10th day of incubation period, with denser biofilm formed in dynamic flow condition. Aerobic, acid-producing and anaerobic bacteria were found in biofilms from both static and dynamic flow. This study shows that biosurfactant F7 with a concentration of 500 μg/mL was able to eradicate biofilm from static and dynamic flow condition up to 78% and 63% respectively. Biosurfactant was able to reduce the number of aerobic and acid-producing bacteria in biofilms, but only able to eliminate anaerobic bacteria from biofilm in static flow condition. Eradication of biofilm only provide an inhibitory effect on corrosion rate of carbon steel ST37 in static flow, whereas the corrosion rate of steel in static flow were 0,1330 mm/year and in dynamic flow were 1,4512 mm/year. It is also revealed that biocorrosion product of Carbon Steel ST37 consist of FeO and Fe2O3. Based on this study, biosurfactant can replace synthetic antimicrobial to eradicate biofilms on steel, but its effect in the corrosion process of steel needs to be investigated further.